AlN, ZnO thin films and AlN/ZnO or ZnO/AlN multilayer structures deposited by PLD for surface acoustic wave applications. Issue 4 (28th January 2015) - Dutheil, P.; Orlianges, J.‐C.; Crunteanu, A.; Catherinot, A.; Champeaux, C.
<x xml:space="preserve">Abstract</x> (0002)‐oriented AlN and ZnO thin films are deposited on C‐sapphire substrates by pulsed laser deposition at 700 °C. Multilayered structures AlN/ZnO and ZnO/AlN are also grown on C‐sapphire and investigated by X‐ray diffraction, scanning electron microscopy and transmission measurements. Ellipsometry analysis is employed to investigate the stack of layers and the optical properties of thin films. This non‐destructive analysis identified an intermediate layer between AlN and ZnO thin films for AlN/ZnO multilayer which didn't change the crystalline structure or piezoelectric properties of the multilayer. Surface acoustic wave velocities are respectively 5060 m s−1 for AlN and 5350 m s−1 for ZnO. In fact, investigations of surface acoustic wave (SAW) devices revealed a similar resonant frequency for both multilayers and in agreement with those measured for ZnO or AlN thin films.